Pemberdayaan Program PEKPPP: Pemantauan dan Evaluasi Kinerja Penyelenggara Pelayanan Publik di Kecamatan Semampir Kota Surabaya - Abellita, Isal (IAI Nasional Laa Roiba Bogor, 2024)
Based on PANRB Ministerial Regulation No. 29/2022 concerning PEKPPP which explains that every agency is obliged to carry out evaluations related to public services in order to improve the quality of public services. Where employees play an important role in achieving these goals. With employees who have abilities according to the criteria referring to Law Number 5 of 2014 concerning Civil Servants, they can run well. This research looks at the problems that occur where employee abilities still need to be improved, from low knowledge in creating documents that employees should be competent and master, many employees in Semampir District who are still not assigned according to their placement, which can hinder the PEKPPP program and objectives. The aim of this research is to describe and explain whether the empowerment of the PEKPPP program in Semampir District, Surabaya City is appropriate. The method used uses a qualitative method and a descriptive approach, where data collection techniques use interviews, literature reviews and documentation. The results of this research show that the empowerment of the PEKPPP program in Semampir sub-district is still not optimal, with indicators that can be improved, starting from employee capabilities, to employee placement that is more in line with the education they have taken.